2008
DOI: 10.1128/mcb.00421-07
|View full text |Cite
|
Sign up to set email alerts
|

Corepressor CtBP and Nuclear Speckle Protein Pnn/DRS Differentially Modulate Transcription and Splicing of the E-Cadherin Gene

Abstract: CtBP is a transcriptional corepressor with tumorigenic potential that targets the promoter of the tumor suppressor gene E-cadherin. Pnn/DRS (Pnn) is a "nuclear speckle"-associated protein involved in mRNA processing as well as transcriptional regulation of E-cadherin via its binding to CtBP. Here, we show that CtBP can recruit Pnn to CtBP-associated complexes, resulting in Pnn-dependent chromatin remodeling at the E-cadherin promoter. In addition, CtBP and Pnn can differentially modulate E-cadherin mRNA splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…8F, G). These observations imply that, as previously shown in CDH1 promoter regulation (Alpatov et al, 2004; Alpatov et al, 2008), PNN and CtBP proteins are directly involved in the regulation of CDX2 promoter activity.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…8F, G). These observations imply that, as previously shown in CDH1 promoter regulation (Alpatov et al, 2004; Alpatov et al, 2008), PNN and CtBP proteins are directly involved in the regulation of CDX2 promoter activity.…”
Section: Resultssupporting
confidence: 86%
“…4G, Cdx2 was transcriptionally downregulated in Pnn-depleted small intestine. Since PNN was previously shown to relieve transcriptional repression activity of CtBPs and thus lead to the derepression of CDH1 ( E-Cadherin ) promoter (Alpatov et al, 2004; Alpatov et al, 2008), we examined whether PNN is directly involved in the promoter regulation of Cdx2 in two human cell lines, OE33 and EcR293 cells, both expressing GFP-tagged PNN protein. Semi-quantitative RT-PCR assay revealed that both OE33 and EcR293 cells express CDX2 , however neither of them expressed CDX1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological functions of Pinin have been mainly discovered in epithelial cell behaviors as its participation in forming desmosome. Besides, its aberrant expression suppressed renal cancer development [14, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…The cell adhesion-related phoshoprotein, pinin/DRS (Pnn), has been shown to directly interact with CtBP1 and interfere with its ability to repress E-cadherin expression (137). CtBPs are also regulated at the post-transcriptional level by the miRNA degradation machinery.…”
Section: Ctbp Role In Emtmentioning
confidence: 99%